Human Lung Cancer (A549) Cell Line Cytotoxicity and Anti-Leishmania major Activity of Carissa macrocarpa Leaves: A Study Supported by UPLC-ESI-MS/MS Metabolites Profiling and Molecular Docking - Mohamed A. A. Orabi; Omaish Salman Alqahtani; Bandar A. Alyami; Ahmed Abdullah Al Awadh; El-Shaymaa; Katsuyoshi Matsunami; Dalia I. Hamdan; Mohamed E. Abouelela (MDPI AG, 2022)
Lung cancer and cutaneous leishmaniasis are critical diseases with a relatively higher incidence in developing countries. In this research, the activity of Carissa macrocarpa leaf hydromethanolic extract and its solvent-fractions (n-hexane, EtOAc, n-butanol, and MeOH) against the lung adenocarcinoma cell line (A549) and Leishmania major was investigated. The MeOH fraction exhibited higher cytotoxic activity (IC50 1.57 ± 0.04 μg/mL) than the standard drug, etoposide (IC50 50.8 ± 3.16 μg/mL). The anti-L. major results revealed strong growth inhibitory effects of the EtOAc fraction against L. major promastigotes (IC50 27.52 ± 0.7 μg/mL) and axenic amastigotes (29.33 ± 4.86% growth inhibition at 100 μg/mL), while the butanol fraction exerted moderate activity against promastigotes (IC50 73.17 ± 1.62), as compared with miltefosine against promastigotes (IC50 6.39 ± 0.29 μg/mL) and sodium stibogluconate against axenic amastigotes (IC50 22.45 ± 2.22 μg/mL). A total of 102 compounds were tentatively identified using UPLC-ESI-MS/MS analysis of the total extract and its fractions. The MeOH fraction was found to contain several flavonoids and flavan-3-ol derivatives with known cytotoxic properties, whereas the EtOAc fractions contained triterpene, hydroxycinnamoyl, sterol, and flavanol derivatives with known antileishmanial activity. Molecular docking of various polyphenolics of the MeOH fraction with HDAC6 and PDK3 enzymes demonstrates high binding affinity of the epicatechin 3-O-β-D-glucopyranoside and catechin-7-O-β-D-glucopyranoside toward HDAC6, and procyanidin C2, procyanidin B5 toward PDK3. These results are promising and encourage the pursuit of preclinical research using C. macrocarpa's MeOH fraction as anti-lung cancer and the EtOAc fraction as an anti-L. major drug candidates.